STRATEGI KOMPENSASI DALAM MENINGKATKAN KEPUASAN KERJA DAN PRODUKTIVITAS SUMBER DAYA MANUSIA - MOYO JALADRI, CHAVID; RACHMAWATI, DITA (JOURNAL KOPERASI DAN MANAJEMEN, 2025)
Purpose – Compensation strategies play a crucial role in enhancing both job satisfaction and human resource productivity. A well-designed compensation package, encompassing competitive salaries, benefits, and performance-based incentives, can motivate employees, foster a sense of value, and ultimately contribute to increased output and organizational success. Therefore, careful consideration of compensation strategies is paramount for achieving optimal workforce performance and fostering a positive work environment. Design/methodology/approach – This study investigates the impact of compensation strategies on enhancing employee job satisfaction and human resource productivity. The design employs a quantitative approach, utilizing surveys and statistical analysis to assess the correlation between various compensation models and employee outcomes. Data will be collected from a sample population within relevant industries to provide empirical evidence supporting the proposed relationship. Findings – The study's findings suggest a significant correlation between compensation strategies and both employee job satisfaction and human resource productivity. Specifically, well-structured and competitive compensation packages appear to positively impact employee morale and motivation, subsequently leading to enhanced performance and output. Further research is warranted to explore the nuances of specific compensation models and their long-term effects on organizational success. Research limitations/implications – This study, while providing insights into the relationship between compensation strategies and both job satisfaction and human resource productivity, is limited by its specific context. Generalizability to other industries or organizational cultures may be constrained. Further research should explore the long-term impacts of the implemented compensation strategies and consider the influence of mediating variables like employee engagement. The findings offer practical implications for organizations seeking to optimize their compensation models for enhanced workforce performance, highlighting the need for tailored approaches based on organizational context. Originality/value – This study investigates the strategic implementation of compensation as a mechanism to enhance both job satisfaction and human resource productivity. The research posits that a well-designed compensation strategy, tailored to employee needs and performance, can significantly contribute to a more satisfied and productive workforce. Consequently, the findings offer valuable insights for organizations seeking to optimize their human capital through effective compensation practices.